Implementasi Fatwa DSN-MUI No.92/DSN/MUI/IV/2014 Tentang Akad Rahn Pada Pembiayaan Wisata Religi Di Pegadaian Syariah Kabupaten Pinrang - Putri Hasma; Wahyuni; Rasyidah Bulqis (Mappideceng:Jurnal Ekonomi Syariah, 2025)
This study aims to determine the implementation of the rahn contract in financing religious tourism at Pegadaian Syariah UPS Pasar Sentral, Pinrang Regency and its compliance with DSN-MUI Fatwa No.92/DSN-MUI/IV/2024. The method used is qualitative descriptive with observation, interview, and documentation techniques.The results of the study indicate that: 1) the religious tourism financing system based on the rahn contract is a practical sharia solution for people who want to perform the Umrah pilgrimage. This program provides easy access to funds through gold collateral, easy installments, and a safe process that is in accordance with sharia principles. 2) Its implementation is in accordance with the fatwa, with transactions that are free of usury, transparent, and only subject to administration and storage fees. However, there are still obstacles such as low public understanding of the rahn contract and limited gold ownership. Pegadaian Syariah addresses this through education and additional services such as gold savings and gold purchases in installments to increase program accessibility for prospective Umrah pilgrims.